Derivation of Rainfall Thresholds for Flash Flood Warning in a Sicilian Basin Using a Hydrological Model. (2016) - Forestieri, A.; Caracciolo, D.; Arnone, E.; Noto, L.V.
Abstract: The damages caused by flash floods are among the most onerous in terms of loss of lives and damage to properties. Derivation of rainfall threshold is one of the approaches commonly used for the development of flash flood warning systems. Specifically, rainfall threshold is the rainfall amount that, for a given basin area and duration, is enough to cause flooding and, therefore, it indicates the maximal sustainable rainfall for a basin. The aim of this paper is deriving flash flood-rainfall thresholds for a Sicilian basin (Italy) throughout a deterministic approach. The conceptual hydrological model TOPDM was used to estimate the amount of rainfall that, for given duration, hydrological initial conditions (i.e., initial soil moisture) and hyetograph type, causes the maximum flow at selected basin outlet. To reduce the uncertainty associated with the non-linearity of the rainfall-discharge process, different initial conditions in terms of soil moisture were considered. Additionally, the rainfall thresholds have been parameterized by taking into account three synthetic hyetographs types characterized by: (i) linearly increasing rainfall intensity, (ii) decreasing intensity and (iii) linearly increasing-decreasing intensity, which are able to describe the typical trends of rainfall events occurring in temperate climates. Results indicated that, for several events, the derived thresholds are able to identify events with peak discharge very similar to the discharge which characterizes the threshold, confirming the goodness of the methodology.